DIVERSIFIKASI USAHA BISNIS - Soleha, Lilis Karnita (Majalah Bisnis & IPTEK, 2021)
The development and improvement of good business is hope for every business. Efforts and measures were always taken to improve its business, for example by increasing the number of outlets, increase production capacity and marketing, as well as enlarge the business scale. In fact there is to diversify its business or business expansion in new business fields. Keywords: business development; scale enterprises